Nile river of gods [videorecording] - Cowling, Tim; McKinnon, Michael; Olmert, Michael; Pye-Smith, Charlie (The Discovery channel., 1994)
An exploration of time and space and life in the times of the Pharaohs and today. Discovers the natural beauty and spirituality of the people. Travels back in time to the scattered kingdoms of upper and lower Egypt. The ways and wildlife 3,000 years ago still survive.